5x+2(x-6)=4(x+1)-3

Simple and best practice solution for 5x+2(x-6)=4(x+1)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+2(x-6)=4(x+1)-3 equation:


Simplifying
5x + 2(x + -6) = 4(x + 1) + -3

Reorder the terms:
5x + 2(-6 + x) = 4(x + 1) + -3
5x + (-6 * 2 + x * 2) = 4(x + 1) + -3
5x + (-12 + 2x) = 4(x + 1) + -3

Reorder the terms:
-12 + 5x + 2x = 4(x + 1) + -3

Combine like terms: 5x + 2x = 7x
-12 + 7x = 4(x + 1) + -3

Reorder the terms:
-12 + 7x = 4(1 + x) + -3
-12 + 7x = (1 * 4 + x * 4) + -3
-12 + 7x = (4 + 4x) + -3

Reorder the terms:
-12 + 7x = 4 + -3 + 4x

Combine like terms: 4 + -3 = 1
-12 + 7x = 1 + 4x

Solving
-12 + 7x = 1 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-12 + 7x + -4x = 1 + 4x + -4x

Combine like terms: 7x + -4x = 3x
-12 + 3x = 1 + 4x + -4x

Combine like terms: 4x + -4x = 0
-12 + 3x = 1 + 0
-12 + 3x = 1

Add '12' to each side of the equation.
-12 + 12 + 3x = 1 + 12

Combine like terms: -12 + 12 = 0
0 + 3x = 1 + 12
3x = 1 + 12

Combine like terms: 1 + 12 = 13
3x = 13

Divide each side by '3'.
x = 4.333333333

Simplifying
x = 4.333333333

See similar equations:

| 2x+4=10+5 | | 9n=536 | | 7=2+t | | 8x+40=90 | | -9(6f-3)= | | 13c-90=5c-34 | | 8/24=6/n | | 7.6(x-2.25)=-15.2 | | 6(10-5x)=45-5(5x+1) | | 64x^2+16x=1 | | 5m-20=4m+16 | | -9(7y-2)= | | 2-3a=8-2(2a+7) | | 2x+3+(2y-2)yi=0 | | 20=2w+4 | | 5.2(x-2.25)=-20.4 | | 18=2h-4 | | 54=-9a | | 4z+2=6z | | 12x^2+2x=5 | | 3(4-c)=-4(c-6) | | -8=a/-10 | | 4.375=7/8(b-4) | | -8=s/-10 | | (2a+9)(5a-6)=0 | | -5-4(6+7y)= | | 4x-(-2)-7x+12=5 | | -6x+21.4=2.2 | | 5n=3n+27 | | 100=p/10 | | -(4y+3)-(-3y-7)=1 | | (8h-1)(2h-3)=0 |

Equations solver categories